From brown, red, and black rice to beer: Changes in phenolics, γ‐aminobutyric acid, and physicochemical attributes. Issue 6 (18th September 2020) - dos Santos, Jaqueline Pozzada; Acunha, Tanize dos Santos; Prestes, Dejalmo Nolasco; Rombaldi, Cesar Valmor; El Halal, Shanise Lisie Mello; Vanier, Nathan Levien
Abstract: Background and objectives: Many breweries have attempted to widen their offers by developing innovative products that meets consumer demands. Brown‐, red‐, and black‐pericarp rice were malted and used for brewing. The color, the physicochemical properties, the γ‐aminobutyric acid (GABA), the phenolics profile, and the free radical scavenging capacity of raw rice, rice malt, and obtained beers were evaluated. Findings: The beer made from black rice malt showed 18 times more nitrogen content when compared to brown rice beer. Regarding GABA content, the beer obtained from red‐pericarp rice was the best, exhibiting more than 20 μg/g. Catechin was detected in beer made with brown‐ and red‐pericarp rice, and protocatechuic acid was detected in beer made from black‐pericarp rice. Beer from black‐pericarp rice kept cyanidin‐3‐O‐glucoside (40.54 μg/ml) above the quantification limit, while other anthocyanins that were initially detected in black rice and its malt were lost during brewing. Conclusions: Work may support future studies regarding the use of pigmented rice genotypes for the development of craft beers with unique physicochemical and nutritional properties. Significance and novelty: The study is in line with current approaches for assessing beer attributes as a function of different rice genotypes, providing knowledge for the scientific world and brewing industry.